Tavola rotonda. Metaromanzo e romanzo editoriale (ENTHYMEMA, 2020)
In this section, we present the transcription of the talks presented in the round table that closed the seminar, as well as the debate in the Q&A session.
Keywords: If on a Winter’s Night a Traveler; metafiction